(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article examines theoretical and practical approaches to assessing the efficiency of small business and entrepreneurial activity. The study analyzes the main economic indicators used in efficiency assessment and identifies their advantages and limitations. Directions for improving the methodology of evaluating the performance of small business entities under modern market conditions are proposed. The article also substantiates the applicability of assessment results in managerial decision-making processes.